Long-term results after resection of primary duodenal adenocarcinoma: A retrospective cohort study. (April 2022) - Jensen, Kristian K.; Storkholm, Jan H.; Chen, Inna; Burgdorf, Stefan K.; Hansen, Carsten P.
Abstract: Background: Radical resection of duodenal adenocarcinoma (DA) offers the possibility of cure. The outcome after operation and adjuvant therapy is mainly based on small numbers due to the low incidence of the disease. We examined the long-term outcome after surgical treatment of DA. Material and methods: This was a retrospective cohort study including all patients undergoing curatively intended resection for histologically confirmed DA at a single University hospital. Long-term survival was examined by the Kaplan-Meier method and compared with the log-rank test. Multivariable Cox proportional hazards regression analysis was applied to adjust for confounding. Results: A total of 96 patients were included. The median follow-up was 3.7 years (IQR 2.9–4.3), during which 18 patients (18.5%) had recurrence and 35 (36.5%) patients had died. The 3- and 5-year overall survival was 66.3% (55.6–76.9%) and 58.2% (46.2–70.2%), respectively. In the multivariable analysis, adjuvant therapy was associated with decreased mortality (HR 0.29, CI 0.11–0.76, P = 0.011) whereas positive lymph node ratio >0.20 was associated with increased mortality. Conclusion: Radical operation for DA has a median overall 5-year-survival of more than 50%. The indication for adjuvant chemotherapy remains to be addressed. Highlights: Retrospective cohort study including all patients undergoing curatively intended resection for histologically confirmed duodenal adenocarcinoma (DA) at a single University hospital. A total of 96 patients were included, median follow-up of 3.7 years Three- and five-year overall survival was 66.3% (55.6–76.9%) and 58.2% (46.2–70.2%) In the multivariable analysis, adjuvant therapy was associated with decreased mortality (HR 0.29, CI 0.15–0.55, P < 0.001)